Modulatory action of Bryonia alba on the immune system in cyclophosphamide induced immunosuppression in BALB/c mice. - Vara Prasad Saka; Godlaveti Vijay Narasimha Kumar; Abanti Goswami; Bharat Kumar Reddy Sanapalli; Pankaj Gupta; Digvijay Verma; Subhash Kaushik (PLoS ONE)
Oxidative stress and inflammation are the most common pathologies in immune-compromised diseases and cancer treatments. The study examined the immune stimulation properties of Bryonia alba (BA) in different potencies (6C, 30C, and 200C) on a BALB/c mice model with a compromised immune system induced by cyclophosphamide (CPM) at a dose of 80 mg/kg. Seventy mice (35 males and 35 females) were randomly distributed into seven groups of 5 animals/sex. Mice treated with different potencies of BA showed notable improvements in various immune parameters, including RBC, WBC, and Hb levels, as well as thymus and phagocytic indices. Treatment also increased serum levels and splenic mRNA expression of IL-2, IL-4, TNF-α, and IFN-γ. The histopathology analysis showed that the spleen sections of the normal group exhibited intact white and red pulp. In contrast, the sections of the CPM group exhibited disrupted and atrophied white pulp. The treatment with BA maintained the spleen in a preserved state, with the white and red pulp remaining intact and a higher density of lymphocytes. The results indicate that BA could serve as a valued immunostimulant agent when administered with chemo-therapy. However, additional research is required to assess the immunostimulatory effects of BA in immune-compromised infections.